Self-repairing new energy tire and production method thereof
By using polyurea-type self-repairing adhesive materials, self-repair microcapsules and meta-aramid staple fibers in new energy tires, the problem of aging and insufficient bonding strength of self-repairing materials in the prior art under high-heat environments is solved, and high structural strength, long service life and excellent self-repairing, heat resistance, bonding and silent performance are achieved.
Patent Information
- Application Number
- CN202411959784.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The self-repairing materials of existing new energy tires age in high-heat environments, the self-repairing performance has decreased, the structural strength is low, the service life is short, and the adhesive strength between the silent cotton and the self-repairing materials is insufficient, so it cannot effectively improve the silent performance.
The polyurea-type self-healing adhesive material is prepared by end amino polyether monomer and 1,6 hexamethylene diisocyanate. Combined with self-healing microcapsules and meta-aramid staple fibers, the impact resistance, heat resistance and bonding strength of the material are improved through the synergistic effect of dynamic cross-linking and microcapsules, and the sound absorption performance is enhanced.
It has achieved high structural strength and long service life of self-repair new energy tires, improved self-repair performance, heat resistance, adhesive performance and silent performance, and improved driving safety and comfort.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of tire production, and in particular to a self-repairing new energy tire and a production method thereof. Background Art
[0002] New energy tires have excellent wear resistance, superior grip, comfortable driving experience and excellent quiet performance. They are an important part of the green, energy-saving and environmentally friendly new energy vehicles that are being vigorously promoted. A layer of adhesive material is applied inside the new energy tire body, and the adhesive material is used to bond the quiet cotton, which can greatly improve the quiet performance of the new energy tire. At the same time, in order to meet driving safety, an adhesive material with self-repairing properties can be selected to bond the quiet cotton while making the new energy tire have self-repairing capabilities. When the new energy vehicle is pierced by a sharp object during driving, the adhesive material with self-repairing properties can quickly block the leak point to avoid gas leakage and improve driving safety.
[0003] The patent with application number 202310386169.4 discloses a disc-type self-repairing sealing material for puncture prevention of new energy vehicle tires, the components of which include modified polyurethane sealing materials and active fillers. The modified polyurethane sealing material is a product obtained by using a sulfide-based compound containing a diamino group to participate in the preparation process of polyurethane. The modified polyurethane sealing material prepared by this method belongs to a kind of high molecular polyurethane variety containing multiple chemical groups, which can be used as a self-repairing sealing material for new energy vehicle tire materials. It has good adhesion with rubber and stronger high temperature resistance and stability, which can fill the defects of poor repair effect and short service life of tire protective agents on the market. However, the above technical solution has the following problems: 1. New energy tires have a heavy load-bearing capacity, and the friction and heat generated during driving are high. Polyurethane materials are very easy to age when used under continuous high heat, and their self-repairing properties are reduced or even lost; 2. The structural strength of polyurethane material itself is low and its service life is still not high; 3. The bonding strength between the self-repairing sealing material and the mute cotton is low. In order to ensure effective bonding, the mute cotton needs to be adhered to the self-repairing sealing material before it dries. However, after the mute cotton is adhered, the solvent in the self-repairing sealing material is not easy to volatilize, resulting in reduced bonding strength; 4. The self-repairing sealing material only has a repairing effect and cannot improve the quietness performance of new energy tires.
[0004] In summary, there is an urgent need to provide a self-repairing new energy tire containing high-performance self-repairing adhesive materials. The self-repairing adhesive materials must have high structural strength and long service life, as well as excellent self-repairing performance, heat resistance, adhesion and quietness. Summary of the invention
[0005] In order to solve at least one of the above technical problems, the present invention provides a method for producing a self-repairing new energy tire, comprising the following steps: Step S100, the amino-terminated polyether monomer, the trimerization catalyst, the chain extender, the rosin acid, the Grubbs catalyst, the self-repairing microcapsule and the meta-aramid staple fiber are mixed and stirred uniformly to obtain component A; the amino-terminated polyether monomer, the disulfide bond-containing monomer, the trimerization catalyst and 1,6-hexamethylene diisocyanate are mixed and stirred uniformly, and reacted at 0 to 50° C. for 1 to 10 hours to obtain component B; the component A and the component B are mixed and stirred uniformly to obtain a self-repairing adhesive material; Step S200, coating the inner surface of the new energy tire body with a self-repairing adhesive material, and then bonding the sound-proofing cotton to the surface of the self-repairing adhesive material to obtain a self-repairing new energy tire.
[0006] In the above technical scheme, step S100 prepares a polyurea self-repairing adhesive material by using terminal amino polyether monomer and 1,6-hexamethylene diisocyanate. The polyurea self-repairing adhesive material has excellent impact resistance and heat resistance, can maintain long-term stable performance in harsh use environments, and has a long service life; the self-repairing microcapsule in component A refers to a microcapsule with phenolic resin or urea-formaldehyde resin as the wall material and dicyclopentadiene as the core material. When the new energy tire is punctured, the wall material of the self-repairing microcapsule is broken, and the liquid dicyclopentadiene inside flows out, and polymerizes under the catalysis of Grubbs catalyst to automatically fill and repair the crack. In addition, the self-repairing microcapsule can also improve the sound absorption performance of the self-repairing material. When the self-repairing microcapsule is in good condition, the liquid dicyclopentadiene inside it can effectively absorb tire noise. When the self-repairing capsule is broken, the liquid dicyclopentadiene flows out, and a cavity is generated inside the self-repairing microcapsule, and the ability to absorb tire noise is further improved; meta-aramid Staple fibers, as reinforcing fillers, can improve the structural strength of self-repairing adhesive materials, effectively limit the deepening of cracks, and enable the self-repairing adhesive materials to have sufficient self-repairing time; rosin acid can significantly improve the bonding strength of self-repairing adhesive materials; component B is a polyurea prepolymer obtained by polymerization of terminal amino polyether monomers, disulfide bond-containing monomers, trimerization catalysts and 1,6-hexamethylene diisocyanate. Through prepolymerization, the reaction heat can be released in advance, delaying the curing time of the self-repairing adhesive material, and providing sufficient operating time for subsequent bonding of silent cotton; the trimerization catalyst can polymerize part of the 1,6-hexamethylene diisocyanate to form multifunctional isocyanates, and the disulfide bond-containing monomers can be grafted onto the multifunctional isocyanates to construct dynamic crosslinking points of the polyurea system, so that the self-repairing adhesive material has the ability to automatically repair cracks; the dynamic crosslinking of disulfide bonds and the synergistic effect of self-repairing microcapsules can quickly self-repair the leaking points of new energy tires, thereby improving driving safety. The new energy tire body in step S200 can be any type of new energy tire to which sound-proofing cotton has not yet been adhered, and the sound-proofing cotton can be any commercially available product.
[0007] Preferably, in step S100, the amino-terminated polyether monomer is at least one of amino-terminated polyoxypropylene ether, amino-terminated polytetrahydrofuran and amino-terminated polyethylene glycol, and the molecular weight of the amino-terminated polyether monomer is 400-2000 g / mol; the extended chain is at least one of 2,4-diethyltoluenediamine, 2,6-diethyltoluenediamine, isophoronediamine, diethanolamine and methylenebis(N,N-dibutyldiphenylamine); the trimerization catalyst is dimethylethanolamine, tetramethylbutanediamine, bis(dimethylaminoethyl) The monomer containing a disulfide bond is at least one of 4,4'-bis(2-amino-6-methylpyrimidinyl) sulfide, 4,4'-diaminodiphenyl disulfide, 4,4'-dihydroxydiphenyl disulfide, 2,2'-diaminodiphenyl disulfide, 6,6'-dihydroxy-2,2'-dinaphthyl disulfide and 3,3'-dihydroxydiphenyl disulfide.
[0008] Preferably, in step S100, the mass ratio of the amino-terminated polyether monomer, the trimerization catalyst, the chain extender, the rosin acid, the Grubbs catalyst, the self-healing microcapsule and the meta-aramid staple fiber is (30-45): (0.01-0.02): (10-25): (15-25): (5-15): (15-45): (15-25); the mass ratio of the amino-terminated polyether monomer, the disulfide bond-containing monomer, the trimerization catalyst and 1,6-hexamethylene diisocyanate is (10-45): (5-15): (0.01-0.02): 65.
[0009] Preferably, in step S100, the preparation of the self-repairing microcapsules comprises the following steps: Step S110, mixing and stirring an emulsifier, an organic solvent, a nano-metal oxide and ammonia water to obtain a reverse microemulsion, adding a silicon source dropwise to the reverse microemulsion under stirring, stirring and reacting at room temperature, filtering, washing and drying after the reaction is completed to obtain nano hollow silica; mixing and stirring ethanol, ammonia water, hexadecyltrimethoxysilane and nano hollow silica to obtain a solid emulsifier; Step S120, phenol, aldehyde and deionized water are mixed and stirred uniformly, the pH value thereof is adjusted to 9-10 with a sodium hydroxide solution, and the mixture is heated to a reaction temperature to react, and a phenolic prepolymer is obtained after the reaction is completed; Step S130, the solid emulsifier, phenolic prepolymer and deionized water are mixed and stirred evenly, the pH value is adjusted to 3.5 with hydrochloric acid solution, and then polyphenol and ammonium chloride are added, and dicyclopentadiene is slowly added dropwise after mixing and stirring evenly. After the addition is completed, ultrasonic emulsification and dispersion are performed, and the temperature is raised to the reaction temperature and the pH value is adjusted to 1-2 with hydrochloric acid solution. After reacting for 2 hours, it is cooled to room temperature, filtered, washed and dried to obtain self-healing microcapsules.
[0010] In the above technical solution, a solid emulsifier with nano hollow silica as the core is introduced into the wall material of the self-repairing microcapsule. The nano hollow silica is hollow inside and can effectively absorb tire noise, further improving the sound absorption effect of the self-repairing microcapsule.
[0011] Preferably, in step S110, the emulsifier is at least one of OP-10, CO-630 and CO-520; the organic solvent is at least one of n-hexane, cyclohexane, n-propane, cyclopropane, n-butane, cyclobutane, n-pentane, cyclopentane, dichloromethane and chloroform; the nano metal oxide is at least one of nano alumina and nano zinc oxide; the silicon source is at least one of ethyl orthosilicate, propyl orthosilicate, butyl orthosilicate and amyl orthosilicate; in step S120, the phenol is at least one of phenol and cresol; the aldehyde is at least one of formaldehyde, paraformaldehyde and acetaldehyde; in step S130, the polyphenol is at least one of resorcinol and tea polyphenols.
[0012] Preferably, in step S110, the mass ratio of emulsifier, organic solvent, nano metal oxide, ammonia water and silicon source is (80-120): (350-2000): (0.05-0.07): (5.5-7.5): (1.5-4.5); the mass ratio of ethanol, ammonia water, hexadecyltrimethoxysilane and nano hollow silica is (90-95): (35-40): (0.15-0.25): 3; in step S120, the mass ratio of phenol, aldehyde and deionized water is 10:5: (25-30); the concentration of sodium hydroxide solution is 5-10wt%; in step S130, the mass ratio of solid emulsifier, phenolic prepolymer, deionized water, polyphenol, ammonium chloride and dicyclopentadiene is (0.5-3): (20-50): (30-100): (1-3): (1-3): (90-150); the concentration of the hydrochloric acid solution is 5-10wt%.
[0013] Preferably, in step S100, the meta-aramid staple fiber is a modified meta-aramid staple fiber with a sheath-core structure, and its preparation comprises the following steps: Step S140, under nitrogen protection, adding meta-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole to dimethylacetamide, stirring evenly to obtain a first solution; adding isophthaloyl chloride to the first solution in multiple times at -25 to -15°C and under nitrogen protection to react, controlling the reaction temperature to be lower than 60°C, and adjusting the pH value to 6 to 8 after the reaction is completed to obtain a meta-aramid polymer solution; Step S150, mixing the meta-aramid polymer solution, calcium chloride, polyethylene glycol 2000 and dimethylacetamide uniformly, and obtaining a spinning sheath solution after vacuum degassing; mixing the meta-aramid polymer solution, calcium chloride, nano hollow silica and dimethylacetamide uniformly, and obtaining a spinning core solution; Step S160, respectively adding the spinning sheath solution and the spinning core solution into a syringe with a coaxial needle, injecting them into a coagulation bath at 60-80° C. through the syringe for coaxial spinning to obtain meta-aramid primary fibers; Step S170, washing and drying the meta-aramid spun fibers to obtain modified meta-aramid fibers with a sheath-core structure, cutting the modified meta-aramid fibers with a sheath-core structure to obtain modified meta-aramid staple fibers with a sheath-core structure having a length of 3 to 6 mm.
[0014] In the above technical scheme, the modified meta-aramid staple fiber with a skin-core structure contains imidazole groups in both the outer skin and the inner core. The introduction of imidazole groups can improve the mechanical properties, thermal stability and flame retardancy of the meta-aramid staple fibers. The inner core contains nano hollow silica, which makes the meta-aramid staple fibers have a sound-absorbing effect, further improving the sound-absorbing performance of the self-healing adhesive material.
[0015] Preferably, in step S140, the molar ratio of m-phenylenediamine, 2-(4-aminophenyl)-5-aminobenzimidazole and dimethylacetamide is (6-7): (3-4): (60-80); the molar ratio of the sum of the moles of m-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole to isophthaloyl chloride is 1:1; the concentration of the m-aramid polymer in the m-aramid polymer solution is 33-38wt%; in step S150, the mass ratio of the m-aramid polymer solution, calcium chloride, polyethylene glycol 2000 and dimethylacetamide is 15:1:1: (20-25); the mass ratio of the m-aramid polymer solution, calcium chloride, nano hollow silica and dimethylacetamide is 15:1: (1-5): (30-50).
[0016] Preferably, in step S160, the injection speed is 0.03 mm / s; the coagulation bath contains 20 wt% DMF and 80 wt% deionized water; and the inner core of the modified meta-aramid staple fiber with a core-skin structure contains 10-50 wt% nano hollow silica.
[0017] The present invention provides a self-repairing new energy tire, which is produced using the above-mentioned production method of the self-repairing new energy tire.
[0018] Compared with the prior art, the present invention has the following beneficial technical effects: 1. A polyurea-type self-healing adhesive material was prepared by using amino-terminated polyether monomers and 1,6-hexamethylene diisocyanate. The polyurea-type self-healing adhesive material has excellent impact resistance and heat resistance, can maintain long-term stable performance in harsh use environments, and has a long service life; 2. The self-repairing microcapsules dispersed in the self-repairing adhesive material cooperate with the Grubbs catalyst to automatically fill and repair the cracks. In addition, the self-repairing microcapsules can also improve the sound absorption performance of the self-repairing material; 3. Meta-aramid staple fibers, as reinforcing fillers, can improve the structural strength of the self-repairing adhesive material, effectively limit the deepening of cracks, and enable the self-repairing adhesive material to have sufficient self-repair time; 4. Rosin acid can significantly improve the bonding strength of self-repairing adhesive materials; 5. The polyurea prepolymer obtained by prepolymerization can release the reaction heat in advance, delay the curing time of the self-repairing adhesive material, and increase the operating time for the subsequent bonding of the silent cotton; the polyurea prepolymer contains disulfide bonds, which form dynamic cross-linking points of the polyurea system, so that the self-repairing adhesive material has the ability to automatically repair cracks; the dynamic cross-linking of disulfide bonds and the synergistic effect of self-repairing microcapsules can quickly self-repair the leaking points of new energy tires, thereby improving driving safety; 6. A solid emulsifier with nano hollow silica as the core is introduced into the wall material of the self-repairing microcapsule. The hollow interior of the nano hollow silica can effectively absorb tire noise, further improving the sound absorption effect of the self-repairing microcapsule; 7. The modified meta-aramid staple fiber with a skin-core structure contains imidazole groups in both the outer skin and the inner core. The introduction of imidazole groups can improve the mechanical properties, thermal stability and flame retardancy of the meta-aramid staple fiber. The inner core contains nano hollow silica, which makes the meta-aramid staple fiber have a sound-absorbing effect, further improving the sound-absorbing performance of the self-repairing adhesive material; In summary, the self-repairing new energy tire provided by the present invention has a high-performance self-repairing adhesive material layer. The self-repairing adhesive material has high structural strength and long service life, as well as excellent self-repairing performance, heat resistance, adhesion performance and quiet performance. DETAILED DESCRIPTION
[0019] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described in detail below in conjunction with specific embodiments. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.
[0020] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.
[0021] Example 1-1 This embodiment prepares a self-repairing microcapsule A, comprising the following steps: Step S110, 120 parts by mass of CO-630, 350 parts by mass of cyclohexane, 0.07 parts by mass of nano zinc oxide and 5.5 parts by mass of ammonia water are mixed and stirred to obtain a reverse microemulsion, 4 parts by mass of butyl orthosilicate are added dropwise to the reverse microemulsion under stirring, and the mixture is stirred and reacted at room temperature for 24 hours. After the reaction is completed, the mixture is filtered, washed and dried to obtain nano hollow silica; 90 parts by mass of ethanol, 40 parts by mass of ammonia water, 0.25 parts by mass of hexadecyltrimethoxysilane and 3 parts by mass of nano hollow silica are mixed and stirred to obtain a solid emulsifier; Step S120, 10 parts by weight of phenol, 5 parts by weight of formaldehyde and 25 parts by weight of deionized water are mixed and stirred uniformly, the pH value thereof is adjusted to 9-10 with a 10 wt % sodium hydroxide solution, the mixture is heated to 70° C. and reacted for 6 hours, and a phenolic prepolymer is obtained after the reaction is completed; Step S130, 3 parts by mass of solid emulsifier, 40 parts by mass of phenolic prepolymer and 50 parts by mass of deionized water are mixed and stirred evenly, 2 parts by mass of resorcinol and 2 parts by mass of ammonium chloride are added after adjusting the pH value to 3.5 with a 10wt% hydrochloric acid solution, and 95 parts by mass of dicyclopentadiene are slowly added dropwise after mixing and stirring evenly. After the addition is completed, ultrasonic emulsification and dispersion are performed, the temperature is raised to 65°C, the pH value is adjusted to 1-2 with a 10wt% hydrochloric acid solution, the reaction is performed for 2 hours, and then cooled to room temperature, filtered, washed and dried to obtain self-repairing microcapsules A; the wall material of the self-repairing microcapsules A contains 15wt% of nano hollow silica.
[0022] Example 1-2 This embodiment prepares a self-repairing microcapsule B, comprising the following steps: Step S110, 80 parts by mass of OP-10, 1500 parts by mass of dichloromethane, 0.05 parts by mass of nano-alumina and 5.5 parts by mass of ammonia water are mixed and stirred to obtain a reverse microemulsion, 4 parts by mass of ethyl orthosilicate are added dropwise to the reverse microemulsion under stirring, and the mixture is stirred and reacted at room temperature for 24 hours. After the reaction is completed, the mixture is filtered, washed and dried to obtain nano hollow silica; 95 parts by mass of ethanol, 35 parts by mass of ammonia water, 0.15 parts by mass of hexadecyltrimethoxysilane and 3 parts by mass of nano hollow silica are mixed and stirred to obtain a solid emulsifier; Step S120, 10 parts by weight of phenol, 5 parts by weight of formaldehyde and 25 parts by weight of deionized water are mixed and stirred uniformly, the pH value thereof is adjusted to 9-10 with a 10 wt % sodium hydroxide solution, the mixture is heated to 70° C. and reacted for 6 hours, and a phenolic prepolymer is obtained after the reaction is completed; Step S130, 0.5 parts by mass of solid emulsifier, 40 parts by mass of phenolic prepolymer and 50 parts by mass of deionized water are mixed and stirred evenly, the pH value is adjusted to 3.5 with a 10wt% hydrochloric acid solution, and then 2 parts by mass of resorcinol and 2 parts by mass of ammonium chloride are added, and after mixing and stirring evenly, 95 parts by mass of dicyclopentadiene are slowly added dropwise, and after the addition is completed, ultrasonic emulsification and dispersion are performed, and the temperature is raised to 65°C and the pH value is adjusted to 1-2 with a 10wt% hydrochloric acid solution. After reacting for 2 hours, it is cooled to room temperature, filtered, washed and dried to obtain self-repairing microcapsules B; the wall material of self-repairing microcapsules B contains 2.86wt% of nano hollow silica.
[0023] Examples 1-3 This embodiment adopts the existing technology to prepare a conventional self-repairing microcapsule C, including the following steps: Step S110, 90 parts by mass of ethanol, 40 parts by mass of ammonia water, 0.25 parts by mass of hexadecyltrimethoxysilane and 3 parts by mass of nano-silicon dioxide are mixed and stirred evenly, and stirred and reacted at room temperature for 24 hours. After the reaction is completed, it is filtered and dried to obtain a solid emulsifier; Step S120, 10 parts by weight of phenol, 5 parts by weight of formaldehyde and 25 parts by weight of deionized water are mixed and stirred uniformly, the pH value thereof is adjusted to 9-10 with a 10 wt % sodium hydroxide solution, the mixture is heated to 70° C. and reacted for 6 hours, and a phenolic prepolymer is obtained after the reaction is completed; Step S130, 3 parts by mass of solid emulsifier, 40 parts by mass of phenolic prepolymer and 50 parts by mass of deionized water are mixed and stirred evenly, the pH value is adjusted to 3.5 with a 10wt% hydrochloric acid solution, and then 2 parts by mass of resorcinol and 2 parts by mass of ammonium chloride are added, and after mixing and stirring evenly, 95 parts by mass of dicyclopentadiene are slowly added dropwise, and after the addition is completed, ultrasonic emulsification and dispersion are performed, and the temperature is raised to 65°C and the pH value is adjusted to 1-2 with a 10wt% hydrochloric acid solution. After reacting for 2 hours, it is cooled to room temperature, filtered, washed and dried to obtain self-healing microcapsules C.
[0024] Example 2-1 This embodiment prepares a modified meta-aramid staple fiber A with a skin-core structure, comprising the following steps: Step S140, under nitrogen protection, adding 6 molar parts of meta-phenylenediamine and 4 molar parts of 2-(4-aminophenyl)-5-aminobenzimidazole to 70 molar parts of dimethylacetamide, stirring evenly to obtain a first solution; adding 10 molar parts of isophthaloyl chloride to the first solution in three times at -25 to -15°C and under nitrogen protection to react, controlling the reaction temperature to be lower than 60°C, and adjusting the pH value to 6 to 8 after the reaction is completed, to obtain a meta-aramid polymer solution with a polymer content of 36.98wt%; Step S150, 15 parts by mass of meta-aramid polymer solution, 1 part by mass of calcium chloride, 1 part by mass of polyethylene glycol 2000 and 25 parts by mass of dimethylacetamide are stirred and mixed uniformly, and a spinning sheath solution is obtained after vacuum degassing; 15 parts by mass of meta-aramid polymer solution, 1 part by mass of calcium chloride, 5 parts by mass of nano hollow silica and 30 parts by mass of dimethylacetamide are mixed and stirred uniformly to obtain a spinning core solution; Step S160, respectively adding the spinning sheath solution and the spinning core solution into a syringe with a coaxial needle, and injecting them into a coagulation bath (containing 20 wt% DMF and 80 wt% deionized water) at 60-80° C. through the syringe for coaxial spinning to obtain meta-aramid primary fibers; Step S170, washing and drying the meta-aramid primary fibers to obtain modified meta-aramid fibers with a sheath-core structure; cutting the modified meta-aramid fibers with a sheath-core structure to obtain modified meta-aramid staple fibers A with a sheath-core structure having a length of 6 mm; the inner core of the modified meta-aramid staple fibers A with a sheath-core structure contains 47.41 wt% of nano hollow silica.
[0025] Example 2-2 This embodiment prepares a modified meta-aramid staple fiber B with a skin-core structure, comprising the following steps: Step S140, under nitrogen protection, adding 6 molar parts of meta-phenylenediamine and 4 molar parts of 2-(4-aminophenyl)-5-aminobenzimidazole to 80 molar parts of dimethylacetamide, stirring evenly to obtain a first solution; adding 10 molar parts of isophthaloyl chloride to the first solution in three times at -25 to -15°C and under nitrogen protection to react, controlling the reaction temperature to be lower than 60°C, and adjusting the pH value to 6 to 8 after the reaction is completed, to obtain a meta-aramid polymer solution with a polymer content of 36.98wt%; Step S150, 15 parts by mass of meta-aramid polymer solution, 1 part by mass of calcium chloride, 1 part by mass of polyethylene glycol 2000 and 25 parts by mass of dimethylacetamide are stirred and mixed uniformly, and a spinning sheath solution is obtained after vacuum degassing; 15 parts by mass of meta-aramid polymer solution, 1 part by mass of calcium chloride, 1 part by mass of nano hollow silica and 30 parts by mass of dimethylacetamide are mixed and stirred uniformly to obtain a spinning core solution; Step S160, respectively adding the spinning sheath solution and the spinning core solution into a syringe with a coaxial needle, and injecting them into a coagulation bath (containing 20 wt% DMF and 80 wt% deionized water) at 60-80° C. through the syringe for coaxial spinning to obtain meta-aramid primary fibers; Step S170, washing and drying the meta-aramid spun fibers to obtain modified meta-aramid fibers with a sheath-core structure; cutting the modified meta-aramid fibers with a sheath-core structure to obtain modified meta-aramid staple fibers B with a sheath-core structure having a length of 3 mm; the inner core of the modified meta-aramid staple fibers B with a sheath-core structure contains 15.27 wt% of nano hollow silica.
[0026] Example 2-3 This embodiment prepares a conventional meta-aramid staple fiber C having a single structure and not containing nano-silicon dioxide and imidazole groups, comprising the following steps: Step S140, under nitrogen protection, adding 10 mole parts of meta-phenylenediamine to 70 mole parts of dimethylacetamide, stirring evenly to obtain a first solution; adding 10 mole parts of isophthaloyl chloride to the first solution in three times at -25 to -15°C and under nitrogen protection to react, controlling the reaction temperature to be lower than 60°C, and adjusting the pH value to 6 to 8 after the reaction is completed, to obtain a meta-aramid polymer solution with a polymer content of 36.68wt%; Step S150, 15 parts by mass of meta-aramid polymer solution, 1 part by mass of calcium chloride, 1 part by mass of polyethylene glycol 2000 and 25 parts by mass of dimethylacetamide are stirred and mixed uniformly, and a spinning solution is obtained after vacuum degassing; Step S160, adding the spinning solution into a syringe, and injecting the solution into a coagulation bath (containing 20 wt% DMF and 80 wt% deionized water) at 60-80° C. through the syringe for spinning to obtain meta-aramid primary fibers; Step S170, washing and drying the meta-aramid spun fibers to obtain modified meta-aramid fibers; cutting the modified meta-aramid fibers to obtain modified meta-aramid staple fibers C with a length of 6 mm.
[0027] Example 3-1 This embodiment produces a self-repairing new energy tire, including the following steps: Step S100, 30 parts by mass of amino-terminated polyoxypropylene ether 2000, 0.01 parts by mass of dimethylethanolamine, 15 parts by mass of 2,4-diethyltoluenediamine, 25 parts by mass of rosin acid, 5 parts by mass of Grubbs catalyst, 15 parts by mass of self-repairing microcapsules A and 15 parts by mass of modified meta-aramid staple fibers A with a core-skin structure are mixed and stirred uniformly to obtain component A; 45 parts by mass of amino-terminated polyoxypropylene ether 2000, 15 parts by mass of 4,4'-bis(2-amino-6-methylpyrimidinyl)sulfide, 0.01 parts by mass of dimethylethanolamine and 65 parts by mass of 1,6-hexamethylene diisocyanate are mixed and stirred uniformly, and reacted at 45°C for 3h to obtain component B; component A and component B are mixed and stirred uniformly to obtain a self-repairing adhesive material; Step S200, coating the inner surface of the new energy tire body with a self-repairing adhesive material, and then bonding the sound-proofing cotton to the surface of the self-repairing adhesive material to obtain a self-repairing new energy tire.
[0028] Example 3-2 This embodiment produces a self-repairing new energy tire, including the following steps: Step S100, 35 parts by mass of amino-terminated polyoxypropylene ether 2000, 0.01 parts by mass of dimethylethanolamine, 20 parts by mass of 2,4-diethyltoluenediamine, 20 parts by mass of rosin acid, 5 parts by mass of Grubbs catalyst, 15 parts by mass of self-repairing microcapsules A and 15 parts by mass of modified meta-aramid staple fibers B with a core-skin structure are mixed and stirred uniformly to obtain component A; 20 parts by mass of amino-terminated polyoxypropylene ether 2000, 5 parts by mass of 4,4'-bis(2-amino-6-methylpyrimidinyl)sulfide, 0.01 parts by mass of dimethylethanolamine and 64 parts by mass of 1,6-hexamethylene diisocyanate are mixed and stirred uniformly, and reacted at 45°C for 3h to obtain component B; component A and component B are mixed and stirred uniformly to obtain a self-repairing adhesive material; Step S200, coating the inner surface of the new energy tire body with a self-repairing adhesive material, and then bonding the sound-proofing cotton to the surface of the self-repairing adhesive material to obtain a self-repairing new energy tire.
[0029] Example 3-3 This embodiment produces a self-repairing new energy tire, including the following steps: Step S100, 45 parts by mass of amino-terminated polyoxypropylene ether 2000, 0.01 parts by mass of dimethylethanolamine, 25 parts by mass of 2,4-diethyltoluenediamine, 15 parts by mass of rosin acid, 5 parts by mass of Grubbs catalyst, 15 parts by mass of self-repairing microcapsules B and 15 parts by mass of modified meta-aramid staple fibers B with a core-skin structure are mixed and stirred uniformly to obtain component A; 25 parts by mass of amino-terminated polyoxypropylene ether 2000, 10 parts by mass of 4,4'-bis(2-amino-6-methylpyrimidinyl) sulfide, 0.01 parts by mass of dimethylethanolamine and 65 parts by mass of 1,6-hexamethylene diisocyanate are mixed and stirred uniformly, and reacted at 45°C for 3h to obtain component B; component A and component B are mixed and stirred uniformly to obtain a self-repairing adhesive material; Step S200, coating the inner surface of the new energy tire body with a self-repairing adhesive material, and then bonding the sound-proofing cotton to the surface of the self-repairing adhesive material to obtain a self-repairing new energy tire.
[0030] Embodiment 3-4 This embodiment produces a self-repairing new energy tire, including the following steps: Step S100, 30 parts by mass of amino-terminated polyoxypropylene ether 2000, 0.01 parts by mass of dimethylethanolamine, 15 parts by mass of 2,4-diethyltoluenediamine, 25 parts by mass of rosin acid, 7 parts by mass of Grubbs catalyst, 25 parts by mass of self-repairing microcapsules A and 25 parts by mass of modified meta-aramid staple fibers A with a core-skin structure are mixed and stirred uniformly to obtain component A; 45 parts by mass of amino-terminated polyoxypropylene ether 2000, 15 parts by mass of 4,4'-bis(2-amino-6-methylpyrimidinyl)sulfide, 0.01 parts by mass of dimethylethanolamine and 65 parts by mass of 1,6-hexamethylene diisocyanate are mixed and stirred uniformly, and reacted at 45°C for 3h to obtain component B; component A and component B are mixed and stirred uniformly to obtain a self-repairing adhesive material; Step S200, coating the inner surface of the new energy tire body with a self-repairing adhesive material, and then bonding the sound-proofing cotton to the surface of the self-repairing adhesive material to obtain a self-repairing new energy tire.
[0031] Embodiment 3-5 This embodiment produces a self-repairing new energy tire, including the following steps: Step S100, 45 parts by mass of amino-terminated polyoxypropylene ether 2000, 0.01 parts by mass of dimethylethanolamine, 25 parts by mass of 2,6-diethyltoluenediamine, 15 parts by mass of rosin acid, 10 parts by mass of Grubbs catalyst, 35 parts by mass of self-repairing microcapsules A and 25 parts by mass of modified meta-aramid staple fibers A with a core-skin structure are mixed and stirred to obtain component A; 25 parts by mass of amino-terminated polyoxypropylene ether 2000, 10 parts by mass of 4,4'-bis(2-amino-6-methylpyrimidinyl) sulfide, 0.01 parts by mass of dimethylethanolamine and 65 parts by mass of 1,6-hexamethylene diisocyanate are mixed and stirred to obtain component B, and reacted at 45°C for 3h to obtain component A; component A and component B are mixed and stirred to obtain a self-repairing adhesive material; Step S200, coating the inner surface of the new energy tire body with a self-repairing adhesive material, and then bonding the sound-proofing cotton to the surface of the self-repairing adhesive material to obtain a self-repairing new energy tire.
[0032] Embodiment 3-6 This embodiment produces a self-repairing new energy tire, including the following steps: Step S100, 45 parts by mass of amino-terminated polyoxypropylene ether 2000, 0.01 parts by mass of dimethylethanolamine, 25 parts by mass of 2,6-diethyltoluenediamine, 15 parts by mass of rosin acid, 15 parts by mass of Grubbs catalyst, 45 parts by mass of self-repairing microcapsules A and 15 parts by mass of modified meta-aramid staple fibers A with a core-skin structure are mixed and stirred to obtain component A; 25 parts by mass of amino-terminated polyoxypropylene ether 2000, 10 parts by mass of 4,4'-bis(2-amino-6-methylpyrimidinyl) sulfide, 0.01 parts by mass of dimethylethanolamine and 65 parts by mass of 1,6-hexamethylene diisocyanate are mixed and stirred to obtain component B, and reacted at 45°C for 3h to obtain component A; component A and component B are mixed and stirred to obtain a self-repairing adhesive material; Step S200, coating the inner surface of the new energy tire body with a self-repairing adhesive material, and then bonding the sound-proofing cotton to the surface of the self-repairing adhesive material to obtain a self-repairing new energy tire.
[0033] Embodiment 3-7 This embodiment produces a self-repairing new energy tire, including the following steps: Step S100, 30 parts by mass of amino-terminated polyoxypropylene ether 400, 0.01 parts by mass of dimethylethanolamine, 10 parts by mass of 2,6-diethyltoluenediamine, 25 parts by mass of rosin acid, 5 parts by mass of Grubbs catalyst, 15 parts by mass of self-repairing microcapsules A and 15 parts by mass of modified meta-aramid staple fibers A with a core-skin structure are mixed and stirred to obtain component A; 10 parts by mass of amino-terminated polyoxypropylene ether 400, 15 parts by mass of 4,4'-bis(2-amino-6-methylpyrimidinyl)sulfide, 0.01 parts by mass of dimethylethanolamine and 65 parts by mass of 1,6-hexamethylene diisocyanate are mixed and stirred to obtain component B, and reacted at 45°C for 3h to obtain component A; component A and component B are mixed and stirred to obtain a self-repairing adhesive material; Step S200, coating the inner surface of the new energy tire body with a self-repairing adhesive material, and then bonding the sound-proofing cotton to the surface of the self-repairing adhesive material to obtain a self-repairing new energy tire.
[0034] Embodiment 3-8 This embodiment produces a self-repairing new energy tire, including the following steps: Step S100, 30 parts by mass of amino-terminated polytetrahydrofuran 1000, 0.02 parts by mass of N, N-dialkyl-3-(dialkylamino)propylamine, 20 parts by mass of isophorone diamine, 20 parts by mass of rosin acid, 5 parts by mass of Grubbs catalyst, 15 parts by mass of self-repairing microcapsules A and 15 parts by mass of modified meta-aramid staple fibers A with a core-skin structure are mixed and stirred to obtain component A; 25 parts by mass of amino-terminated polytetrahydrofuran 1000, 5 parts by mass of 4,4'-diaminodiphenyl disulfide, 0.01 parts by mass of N, N-dialkyl-3-(dialkylamino)propylamine and 65 parts by mass of 1,6-hexamethylene diisocyanate are mixed and stirred to obtain component B, and reacted at 45° C. for 3 hours to obtain component A; component A and component B are mixed and stirred to obtain a self-repairing adhesive material; Step S200, coating the inner surface of the new energy tire body with a self-repairing adhesive material, and then bonding the sound-proofing cotton to the surface of the self-repairing adhesive material to obtain a self-repairing new energy tire.
[0035] Embodiment 3-9 This embodiment produces a self-repairing new energy tire, including the following steps: Step S100, vulcanization molding to prepare a new energy tire body; Step S100, 30 parts by mass of amino-terminated polyethylene glycol 2000, 0.01 parts by mass of tetramethylbutylene diamine, 10 parts by mass of diethanolamine, 25 parts by mass of rosin acid, 5 parts by mass of Grubbs catalyst, 15 parts by mass of self-repairing microcapsules A and 15 parts by mass of modified meta-aramid staple fibers A with a core-skin structure are mixed and stirred to obtain component A; 45 parts by mass of amino-terminated polyethylene glycol 2000, 15 parts by mass of 2,2'-diaminodiphenyl disulfide, 0.02 parts by mass of tetramethylbutylene diamine and 65 parts by mass of 1,6-hexamethylene diisocyanate are mixed and stirred to obtain component B, and reacted at 45°C for 3h to obtain component B; component A and component B are mixed and stirred to obtain a self-repairing adhesive material; Step S200, coating the inner surface of the new energy tire body with a self-repairing adhesive material, and then bonding the sound-proofing cotton to the surface of the self-repairing adhesive material to obtain a self-repairing new energy tire.
[0036] Embodiment 3-10 This embodiment produces a self-repairing new energy tire. The difference from Embodiment 3-1 is that in step S100, the self-repairing microcapsule A is replaced with conventional self-repairing microcapsule C, and the solid emulsifier of the conventional self-repairing microcapsule contains only solid nano-silicon dioxide.
[0037] Example 3-11 This embodiment produces a self-repairing new energy tire. The difference from Example 3-1 is that in the self-repairing adhesive material, the modified meta-aramid staple fiber A with a skin-core structure is changed to a conventional meta-aramid staple fiber C. The conventional meta-aramid staple fiber C has a single structure and does not contain nano-silica and imidazole groups.
[0038] Comparative Example 1 This comparative example produces a self-repairing new energy tire, which is different from Example 3-1 in that in step S100, the self-repairing adhesive material does not contain Grubbs catalyst and self-repairing microcapsule A.
[0039] Comparative Example 2 This comparative example produces a self-repairing new energy tire, which is different from Example 3-1 in that the self-repairing adhesive material does not contain modified meta-aramid staple fiber A with a skin-core structure.
[0040] Comparative Example 3 This comparative example produces a self-repairing new energy tire, which is different from Example 3-1 in that the self-repairing adhesive material does not contain Grubbs catalyst, self-repairing microcapsule A and modified meta-aramid staple fiber A with a skin-core structure.
[0041] Comparative Example 4 This comparative example produces a self-repairing new energy tire, which is different from Example 3-1 in that when the self-repairing adhesive material is prepared, component A does not contain rosin acid.
[0042] Performance Testing 1. The tensile strength and elongation at break of the self-repairing adhesive materials in Examples 3-1 to 3-11 and Comparative Examples 1 to 4 were tested using GB / T-528. The adhesion of the self-repairing adhesive materials in Examples 3-1 to 3-11 and Comparative Examples 1 to 4 was tested using GB / T30774. The results are shown in Table 1.
[0043] As can be seen from Table 1, when preparing the self-healing adhesive material, Examples 3-1 to 3-11, in which component A simultaneously contains Grubbs catalyst, self-healing capsules, meta-aramid staple fibers and rosin acid, have excellent tensile strength and bonding properties; Comparative Example 1 is to remove the self-healing microcapsule A in Example 3-1, and its tensile strength and bonding force are reduced; Comparative Example 2 is to remove the modified meta-aramid staple fiber A of the skin-core structure in Example 3-1, and its tensile strength is reduced; Comparative Example 3 is to remove the self-healing microcapsule A and the modified meta-aramid staple fiber A of the skin-core structure in Example 3-1, and its tensile strength is reduced and the bonding performance is reduced; Comparative Example 4 is to remove the rosin acid in component A in Example 3-1, and its bonding performance is greatly reduced.
[0044] 2. The self-repairing properties of the self-repairing adhesive materials in Examples 3-1 to 3-11 and Comparative Examples 1 to 4 were tested at room temperature and high temperature. The test results are shown in Table 2.
[0045] As can be seen from Table 2, when preparing the self-healing adhesive material, Examples 3-1 to 3-11 and Comparative Example 4, in which component A contains Grubbs catalyst, self-healing microcapsules and meta-aramid staple fibers at the same time, have higher self-healing rates at room temperature and high temperature than Comparative Examples 1 to 3.
[0046] 3. The tire noise test method of GB / T32789-2016 was used to measure the tire noise of the new energy tires in Examples 3-1 to 3-11 and Comparative Examples 1 to 4. The test results are shown in Table 3.
[0047] As can be seen from Table 3, in Examples 3-1 to 3-9 and Comparative Example 4, the self-repairing microcapsule wall material in the self-repairing adhesive material contains nano hollow silica, and the modified meta-aramid staple fiber with a skin-core structure contains imidazole groups and nano hollow silica, and has excellent sound absorption performance; Example 3-10 replaces the nano hollow silica in the self-repairing capsule wall material in Example 3-1 with conventional solid nano silica, so its sound absorption performance is lower than that of Example 3-1; Example 3-11 replaces the modified meta-aramid staple fiber with a skin-core structure in Example 3-1 with conventional meta-aramid staple fiber, so its sound absorption performance is lower than that of Example 3-1. Comparative Example 1 does not contain self-repairing microcapsules, so its sound absorption performance is significantly reduced; Comparative Example 2 does not contain modified meta-aramid staple fibers with a skin-core structure in the self-repairing adhesive material, so its sound absorption performance is significantly reduced; Comparative Example 3 does not contain self-repairing microcapsules and modified meta-aramid staple fibers with a skin-core structure, so its sound absorption performance is the lowest.
[0048] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement modes and shall be included in the protection scope of the present invention.
Claims
1. A method for producing a self-repairing new energy tire, characterized in that: The following steps are involved: Step S100, the amino-terminated polyether monomer, the trimerization catalyst, the chain extender, the rosin acid, the Grubbs catalyst, the self-repairing microcapsule and the meta-aramid staple fiber are mixed and stirred uniformly to obtain component A; the amino-terminated polyether monomer, the disulfide bond-containing monomer, the trimerization catalyst and 1,6-hexamethylene diisocyanate are mixed and stirred uniformly, and reacted at 0 to 50° C. for 1 to 10 hours to obtain component B; the component A and the component B are mixed and stirred uniformly to obtain a self-repairing adhesive material; Step S200, coating the inner surface of the new energy tire body with a self-repairing adhesive material, and then bonding the sound-proofing cotton to the surface of the self-repairing adhesive material to obtain a self-repairing new energy tire.
2. The method for producing a self-repairing new energy tire according to claim 1, characterized in that: In step S100, the amino-terminated polyether monomer is at least one of amino-terminated polyoxypropylene ether, amino-terminated polytetrahydrofuran and amino-terminated polyethylene glycol, and the molecular weight of the amino-terminated polyether monomer is 400-2000 g / mol; the extended chain is at least one of 2,4-diethyltoluenediamine, 2,6-diethyltoluenediamine, isophoronediamine, diethanolamine and methylenebis(N,N-dibutyldiphenylamine); the trimerization catalyst is dimethylethanolamine, tetramethylbutylene diamine, bis(dimethylaminoethyl) ether, At least one of triethylamine, N,N-dialkyl-3-(dialkylamino)propylamine, tris(dimethylamino)phenol, tris(dimethylaminomethyl)phenol and dibutyltin dilaurate; the disulfide bond-containing monomer is at least one of 4,4'-bis(2-amino-6-methylpyrimidinyl)sulfide, 4,4'-diaminodiphenyl disulfide, 4,4'-dihydroxydiphenyl disulfide, 2,2'-diaminodiphenyl disulfide, 6,6'-dihydroxy-2,2'-dinaphthyl disulfide and 3,3'-dihydroxydiphenyl disulfide.
3. The method for producing a self-repairing new energy tire according to claim 1, characterized in that: In step S100, the mass ratio of the amino-terminated polyether monomer, the trimerization catalyst, the chain extender, the rosin acid, the Grubbs catalyst, the self-healing microcapsule and the meta-aramid staple fiber is (30-45): (0.01-0.02): (10-25): (15-25): (5-15): (15-45): (15-25); the mass ratio of the amino-terminated polyether monomer, the disulfide bond-containing monomer, the trimerization catalyst and 1,6-hexamethylene diisocyanate is (10-45): (5-15): (0.01-0.02):
65.
4. The method for producing a self-repairing new energy tire according to claim 1, characterized in that: In step S100, the preparation of the self-repairing microcapsules includes the following steps: Step S110, mixing and stirring an emulsifier, an organic solvent, a nano-metal oxide and ammonia water to obtain a reverse microemulsion, adding a silicon source dropwise to the reverse microemulsion under stirring, stirring and reacting at room temperature, filtering, washing and drying after the reaction is completed to obtain nano hollow silica; mixing and stirring ethanol, ammonia water, hexadecyltrimethoxysilane and nano hollow silica to obtain a solid emulsifier; Step S120, phenol, aldehyde and deionized water are mixed and stirred uniformly, the pH value thereof is adjusted to 9-10 with a sodium hydroxide solution, and the mixture is heated to a reaction temperature to react, and a phenolic prepolymer is obtained after the reaction is completed; Step S130, the solid emulsifier, phenolic prepolymer and deionized water are mixed and stirred evenly, the pH value is adjusted to 3.5 with hydrochloric acid solution, and then polyphenol and ammonium chloride are added, and dicyclopentadiene is slowly added dropwise after mixing and stirring evenly. After the addition is completed, ultrasonic emulsification and dispersion are performed, and the temperature is raised to the reaction temperature and the pH value is adjusted to 1-2 with hydrochloric acid solution. After reacting for 2 hours, it is cooled to room temperature, filtered, washed and dried to obtain self-healing microcapsules.
5. The method for producing a self-repairing new energy tire according to claim 4, characterized in that: In step S110, the emulsifier is at least one of OP-10, CO-630 and CO-520; the organic solvent is at least one of n-hexane, cyclohexane, n-propane, cyclopropane, n-butane, cyclobutane, n-pentane, cyclopentane, dichloromethane and chloroform; the nano metal oxide is at least one of nano alumina and nano zinc oxide; the silicon source is at least one of ethyl orthosilicate, propyl orthosilicate, butyl orthosilicate and amyl orthosilicate; in step S120, the phenol is at least one of phenol and cresol; the aldehyde is at least one of formaldehyde, paraformaldehyde and acetaldehyde; in step S130, the polyphenol is at least one of resorcinol and tea polyphenols.
6. The method for producing a self-repairing new energy tire according to claim 4, characterized in that: In step S110, the mass ratio of emulsifier, organic solvent, nano metal oxide, ammonia water and silicon source is (80-120): (350-2000): (0.05-0.07): (5.5-7.5): (1.5-4.5); the mass ratio of ethanol, ammonia water, hexadecyltrimethoxysilane and nano hollow silica is (90-95): (35-40): (0.15-0.25): 3; in step S120, the mass ratio of phenol, aldehyde and deionized water is 10:5: (25-30); the concentration of sodium hydroxide solution is 5-10wt%; in step S130, the mass ratio of solid emulsifier, phenolic prepolymer, deionized water, polyphenol, ammonium chloride and dicyclopentadiene is (0.5-3): (20-50): (30-100): (1-3): (1-3): (90-150); the concentration of the hydrochloric acid solution is 5-10wt%.
7. The method for producing a self-repairing new energy tire according to claim 1, characterized in that: In step S100, the meta-aramid staple fiber is a modified meta-aramid staple fiber with a sheath-core structure, and its preparation includes the following steps: Step S140, under nitrogen protection, adding meta-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole to dimethylacetamide, stirring evenly to obtain a first solution; adding isophthaloyl chloride to the first solution in multiple times at -25 to -15°C and under nitrogen protection to react, controlling the reaction temperature to be lower than 60°C, and adjusting the pH value to 6 to 8 after the reaction is completed to obtain a meta-aramid polymer solution; Step S150, mixing the meta-aramid polymer solution, calcium chloride, polyethylene glycol 2000 and dimethylacetamide uniformly, and obtaining a spinning sheath solution after vacuum degassing; mixing the meta-aramid polymer solution, calcium chloride, nano hollow silica and dimethylacetamide uniformly, and obtaining a spinning core solution; Step S160, respectively adding the spinning sheath solution and the spinning core solution into a syringe with a coaxial needle, injecting them into a coagulation bath at 60-80° C. through the syringe for coaxial spinning to obtain meta-aramid primary fibers; Step S170, washing and drying the meta-aramid spun fibers to obtain modified meta-aramid fibers with a sheath-core structure, cutting the modified meta-aramid fibers with a sheath-core structure to obtain modified meta-aramid staple fibers with a sheath-core structure having a length of 3 to 6 mm.
8. The method for producing a self-repairing new energy tire according to claim 7, characterized in that: In step S140, the molar ratio of m-phenylenediamine, 2-(4-aminophenyl)-5-aminobenzimidazole and dimethylacetamide is (6-7): (3-4): (60-80); the molar ratio of the sum of the moles of m-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole to isophthaloyl chloride is 1:1; the concentration of the m-aramid polymer in the m-aramid polymer solution is 33-38wt%; in step S150, the mass ratio of the m-aramid polymer solution, calcium chloride, polyethylene glycol 2000 and dimethylacetamide is 15:1:1: (20-25); the mass ratio of the m-aramid polymer solution, calcium chloride, nano hollow silica and dimethylacetamide is 15:1: (1-5): (30-50).
9. The method for producing a self-repairing new energy tire according to claim 7, characterized in that: In step S160, the injection speed is 0.03 mm / s; the coagulation bath contains 20 wt% of DMF and 80 wt% of deionized water; and the inner core of the modified meta-aramid staple fiber with a core-skin structure contains 10 to 50 wt% of nano hollow silica.
10. A self-repairing new energy tire, characterized in that: The tire is produced by the method for producing a self-repairing new energy tire as described in any one of claims 1 to 9.
Citation Information
Patent Citations
Disc-covering type self-repairing sealing material for preventing new energy automobile tire from being punctured and preparation method of disc-covering type self-repairing sealing material
CN116396605A
Cited By
Self-repairing composite foam material and preparation method thereof
CN121537671A